An Evaluation of World Bank Research, 1998-2005 - Banerjee, Abhijit (World Bank, Washington, DC, 2014)
This evaluation of World Bank research between 1998 and 2005 was carried out by a panel consisting of Abhijit Banerjee (MIT), Angus Deaton (Princeton, chair), Nora Lustig (UNDP), and Kenneth Rogoff (Harvard.) The panel selected a large random sample of research projects, which were read and assessed by a team of 25 evaluators. Panel members also solicited views from current and past Bank staff, as well as from policy makers and academics in developing countries. Based on the evidence the authors assembled, the interviews the authors conducted, and their own consideration, the panel concluded that the World Bank needs a research department, and that its research needs cannot be fully met by hiring in from the outside. Research is a central part of quality control in the Bank, and is crucial to its claim to be 'Knowledge Bank.' Without a research-based ability to learn from its projects and policies, the Bank could not maintain its role as the world's leading development agency. The 2.5 percent of its administrative budget that the Bank spends on research is surely too low given the multiplicity of tasks that research is expected to fulfill, including the generation of new knowledge about development, the collection and dissemination of data, the generation of knowledge to support guide Bank strategy, operational support, and capacity building in client countries. As the world becomes richer, and already today among middle income countries, the need for high-quality, research-based advice will only become stronger as the need for Bank lending diminishes.